Специфіка мотиваційного складника споживчої поведінки страхувальників - Федорова, Ніна; Федорова, Нина; Fedorova, Nina (My University, 2016)
Споживча поведінка страхувальників має такі специфічні риси, як нематеріальний характер страхових послуг, високий рівень недовіри до страхових компаній, необізнаність населення в цілому щодо наслідків від купівлі страхового поліса. Визначено, що специфічними детермінантами, які характеризують споживачів страхових послуг, є чуттєвість до ризиків, рівень доходу, довіра до страхових компаній, ціна страхового продукту, рівень страхової культури. Отже, робимо висновок, що складність задоволення потреб споживача страхових послуг підсилюється поширеністю негативних факторів у суспільстві. Усе це перетворює мотиви до придбання страхового поліса в протилежне бажання – не мати жодних стосунків зі страховими компаніями взагалі. Потребительское поведение страхователей имеет свои специфические черты: нематериальный характер страховых услуг, достаточно высокий уровень недоверия к страховым компаниям, неграмотность населения в целом относительно положительных результатов от покупки страхового полиса. Определены следующие составляющие, определяющие поведение страхователей: первая – чувствительность к рискам, вторая – уровень дохода потребителя, третья – доверие к страховым компаниям; четвертая – уровень страховой культуры, который показывает знание людей о сущности понятия «страхование» и осознание необходимости такого вида деятельности для каждой личности. В результате исследования делаем вывод, что сложность удовлетворения потребностей потребителя страховых услуг усиливается распространенность негативных факторов в обществе. Все это превращает мотивы к приобретению страхового полиса в противоположное желание – не иметь никаких отношений со страховыми компаниями вообще. The consumer behaviour of the insured has its specific features. For example, the intangible nature of insurance services, quite high level of distrust to insurance companies, the population’s ignorance in general about the positive effects of buying an insurance policy. All this leads to the formation of the specific relationship between the insurance market participants. The following components that determine the behaviour of policyholders are identified. The first determinant that determines behaviour of the consumer of insurance services is sensitivity to risks, i.e. the ability of a particular subject to assess and percept the influence of external or internal environment that may lead to negative consequences. The second determinant is the consumers’ income level. It is assumed that if the wealthy segments of the population are the main consumers of insurance services, it is clear that low income will be on the contrary a negative motivation to use insurance services. The third determinant is considered to be confidence in insurance companies. Our country is characterized by a high level of distrust to any social and economic institutions. The fourth determinant is the insurance culture level that characterizes the knowledge level of essence of the concept «insurance» and awareness of the need of this type of activity for each individual. Another complex determinant which is in a way related to the previous ones is price of the insurance products. In terms of the low income level and insurance culture this determinant is closely related to the other three. Thus, the complexity of satisfying the customer of insurance services is amplified by the spread of negative factors in the society. All this turns the motives to purchase insurance pole into the opposite desire – not to have any relations with insurance companies at all.
Specifics of the Motivational Component of the Consumer Behaviour of the Insured
Keywords: страхування; страхувальник; страхова культура; страхова послуга; негативна мотивація; страхование; страхователь; страховая культура; страховая услуга; негативная мотивация; insurance; the insured; insurance culture; insurance service; negative motivation